Bridging the Gap between SERS Ehnancement and Reproducibility by Salt Aggregated Silver Nanoparticles - MCCABE, EITHNE (My University, 2015)
Silver colloid based nanostructures are a very common means of achieving strong SERS signals. This is due to the hot spots that are formed in between the nanoparti‐ cles, as well as their ease of synthesis. They are frequent‐ ly dismissed, however, as irreproducible when compared to other metal nanostructures, due to the random nature of their formation in a solution. Silver nanoparticle substrates or carefully constructed arrays can be made to be uniform, but they often require a large amount of time to produce, as well as expensive equipment. We will show that by making some adjustments to the experimen‐ tal setup, silver colloids that have been aggregated to form large flakes can offer both the enhancement factor and reproducibility of many other more expensive and complicated SERS techniques. Silver colloids aggregated into large flake-like structures have been investigated for their surface-enhanced Raman spectroscopy (SERS) properties. These flakes have been imaged using scanning electron microscopy (SEM) and have also been characterized using UV/Vis spectroscopy. They have been highlighted as a cheap and simple means or achieving large Raman enhancement with strong reproducibility, especially when compared to many common methods of substrate fabrication that are more difficult to fabricate. Detection of Rhodamine 6G at a concentration of 5x10 -13 M has been achieved, as well as xanthopterin at a concentration of 5x10 -9 M
PUBLISHED
Keywords: SERS, nanoparticles, Raman, reproducibility; SERS, nanoparticles, Raman, reproducibility; Nanoscience & Materials